Serious Adverse Events after a Single Shot of Intrathecal Morphine: A Case Series and Systematic Review - Mark V. Koning; Elmer Reussien; Beatrijs A. N. Vermeulen; Svenja Zonneveld; Elsbeth M. Westerman; Jurgen C. de Graaff; Bernard M. Houweling (Pain Research and Management)
Background. The dose of intrathecal morphine is important because of its narrow therapeutic range. Due to a compounding error, pharmacy-compounded, ready-to-use syringes contained 1 mg ml−1 morphine instead of the intended 50 mcg ml−1. Six patients consequently received this twenty-fold dose. This study aims to describe the serious adverse events in these six patients and a systematic review is added to describe the characteristics of serious adverse events after intrathecal morphine. Methods. A retrospective case series described all six patients that received the erroneous morphine intrathecally for analgesia after laparoscopic segmental colonic resections. The patients’ charts were reviewed for the occurrence, timing, duration and management of adverse events, the vital signs at the night after surgery, and length of hospital stay. A systematic review investigated characteristics of serious adverse events after intrathecal morphine in a perioperative setting. Results. Four patients had a serious adverse event, which was respiratory depression combined with somnolence (n = 3) and hypotension (n = 1). The review yielded 63 cases with serious adverse events, predominantly somnolence and/or respiratory depression. The onset occurred between 2 and 24 hours after injection. The severity of symptoms varied and life-threatening respiratory depression only occurred after a dose >900 mcg or when potentiating medication was used. Naloxone did not affect analgesia. No prolonged sequalae occurred. Conclusion. This study reveals that respiratory depression and somnolence are the predominant serious adverse events after intrathecal morphine in a perioperative setting and demonstrated a large variation in the presentation of symptoms.